Intravenous Immunoglobulin Therapy Restores the Quantity and Phenotype of Circulating Dendritic Cells and CD4+ T Cells in Children With Acute Kawasaki Disease - Wang, Nana; Chen, Zhongyue; Zhang, Fan; Zhang, Qianwen; Sun, Ling; Lv, Haitao; Wang, Bo; Shen, Jie; Zhou, Xufang; Chen, Feiyan; Zhang, Binwei; Meng, Lijun; et al. (Frontiers in Immunology, 2022)
Abstract Background: Intravenous immunoglobulin (IVIG) showed its therapeutic efficacy on Kawasaki disease (KD). However, the mechanisms by which it reduces systemic inflammation are not completely understood. Dendritic cells (DCs) and T cells play critical roles in the pathogenic processes of immune disorders. Assessing the quantity of DC subsets and T cells and identifying functional molecules present on these cells, which provide information about KD, in the peripheral blood may provide new insights into the mechanisms of immunoglobulin therapy. Methods: In total, 54 patients with KD and 27 age-matched healthy controls (HCs) were included in this study. The number, percentage, and phenotype of DC subsets and CD4+ T cells in peripheral blood were analysed through flow cytometry. Results: Patients with KD exhibited fewer peripheral DC subsets and CD4+ T cells than HCs. Human leucocyte antigen-DR (HLA-DR) expression was reduced on CD1c+ myeloid DCs (CD1c+ mDCs), whereas that on plasmacytoid DCs (pDCs) did not change significantly. Both pDCs and CD1c+ mDCs displayed significantly reduced expression of co-stimulatory molecules, including CD40, CD86. pDCs and CD1c+ mDCs presented an immature or tolerant phenotype in acute stages of KD. Number of circulating pDC and CD1c+ mDC significantly inversely correlated with plasma interleukin-6 (IL-6) levels in KD patients pre-IVIG treatment. No significant differences were found concerning the DC subsets and CD4+ T cells in patients with KD with and without coronary artery lesions. Importantly, these altered quantity and phenotypes on DC subsets and CD4+ T cells were restored to a great extent post-IVIG treatment. T helper (Th) subsets including Th1 and Th2 among CD4+ T cells did not show alteration pre- and post-IVIG treatment, although the Th1-related cytokine IFN-γ level in plasma increased dramatically in patients with KD pre-IVIG treatment. Conclusions: pDCs and CD1c+ mDCs presented an immature or tolerant phenotype in acute stages of KD, IVIG treatment restored the quantity and functional molecules of DCs and CD4+ T cells to distinct levels in vivo, indicating the involvement of DCs and CD4+ T cells in the inflammation in KD. The findings provide insights into the immunomodulatory actions of IVIG in KD.